Effect of charge distribution on the stability of nano-dispersions - Kallay, Nikola (Array, 2009)
Summary: In the course of aggregation of very small colloid particles, i.e. nano-particles, the overlap of the diffuse layers is almost complete, so that one cannot apply the common DLVO theory. Since nano-particles are small compared to the extent of the diffuse layer, the process is considered in the same way as for two interacting ions. Therefore, the Bronsted concept based on the Transition State Theory was applied. In this work the effect of charge distribution among nano-particles was examined. Results of numerical simulation show that wider charge distribution causes substantial decrease in the stability of nano-dispersions